2021
DOI: 10.2319/052620-480.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intraoral application of antiseptics and fluorides during orthodontic treatment on corrosion and mechanical characteristics of nickel-titanium alloy in orthodontic appliances

Abstract: Objectives To explore whether the commercial agents recommended for controlling dental biofilm formation had a significant effect in vivo on mechanical and corrosion properties of nickel-titanium (NiTi) alloy. Materials and Methods NiTi archwires (dimensions 0.508 × 0.508 mm) were collected from 36 orthodontic patients aged 13–42 years after a 3-month intraoral exposure. Three experimental groups were formed: (1) subjects con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…This, together with the fact that commercial mouthwashes with fluorine-containing compounds do not cause the dissolution of Ti-O but a release of Ni-ions [ 43 ] suggests that the investigated mouthwashes behave in the same fashion. The opposite trends on surface roughness which is observed for fluoride media are in agreement with the literature data that fluoride compound-containing media can induce both an increase [ 30 , 31 , 32 ] and a decrease [ 33 ] in surface roughness. Our findings suggest that these diverging trends are a consequence of preferred corrosion locations, relative to the mean plane.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This, together with the fact that commercial mouthwashes with fluorine-containing compounds do not cause the dissolution of Ti-O but a release of Ni-ions [ 43 ] suggests that the investigated mouthwashes behave in the same fashion. The opposite trends on surface roughness which is observed for fluoride media are in agreement with the literature data that fluoride compound-containing media can induce both an increase [ 30 , 31 , 32 ] and a decrease [ 33 ] in surface roughness. Our findings suggest that these diverging trends are a consequence of preferred corrosion locations, relative to the mean plane.…”
Section: Discussionsupporting
confidence: 91%
“…These techniques allow detection of nanometric changes on the surface and quantification of these changes by surface roughness parameters. It is reported that both fluorine- and chlorine-containing compounds in media can cause a considerable change of the surface topography [ 10 , 26 , 30 , 31 , 32 , 33 ] and that the intensity of the corrosion processes can depend on the surface topography [ 18 , 23 , 31 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sample size was calculated according ( Arkin., 1984) and ( Belasic et al, 2021) using Eqs [ 7 , 8 ]. :…”
Section: Methodsmentioning
confidence: 99%
“…The sample size was calculated using a computer program SPSS software for windows version 22.0 (Statistical Package for Social Science, Armonk, NY: IBM Corp), G Power version 3.1.9 based on a previous study [ 8 ]. For the present study, the power sample size was more than 80%, the significance level was 0.05, the confidence interval was 95%, and the actual power was 95.40%.…”
Section: Methodsmentioning
confidence: 99%
“…In fixed orthodontic treatment, changes in the mechanical characteristics of the archwires may cause negative effects on the mechanical properties or working properties and, consequently, disturb the clinical progress and outcome [6]. When the archwires are placed in the brackets, cyclical forces during mastication can produce fatigue and limit the wire's lifespan [7].…”
Section: Introductionmentioning
confidence: 99%